A low porosity graphite material and its preparation method and application
Patent Information
- Application Number
- CN202410738787.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-06-07
AI Technical Summary
The porosity of existing graphite boat materials is high, resulting in increased coating pretreatment time when used under high temperature and high vacuum conditions, which affects production efficiency and may lead to uneven coating and rupture, affecting product quality.
By purifying and modifying natural scale graphite, including impregnation of acid potassium permanganate solution, hydrothermal reaction, silane modification and 2,3,4-trimethyl-2-pentene grafting reaction, low porosity graphite material is formed.
It significantly reduces the porosity of graphite materials, improves its conductivity, mechanical properties and heat resistance, and ensures that the resistance change rate is small and the thermal expansion coefficient is low at high temperatures. It is suitable for the preparation of high-performance graphite boat sheets.
Smart Images

Figure BDA0004882575610000161
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of graphite materials, and in particular relates to a low-porosity graphite material and a preparation method and application thereof. Background Art
[0002] Plasma enhanced chemical vapor deposition (PECVD) is one of the most commonly used coating processes and is widely used in the production of semiconductors and solar cells. In the industrial process, graphite boats are used as PECVD tools.
[0003] With the growing demand for cost reduction and efficiency improvement in the photovoltaic market, the production capacity of tubular PECVD equipment is also increasing. As a key loading tool in the tubular PECVD production process, the number of silicon wafers coated in a single large-capacity graphite boat has increased from the original 300 or 400 to about 600 now, and the length of the boat has reached more than 2 meters, so the performance requirements for the graphite boat are gradually increasing.
[0004] Generally, when choosing a graphite boat, the following points should be considered: 1. High density and low porosity, especially fewer open pores; 2. Good electrical conductivity, especially stable resistivity under high temperature conditions; 3. Uniform material, especially to avoid various defects such as cracks, sand holes and deformation; 4. Higher purity. Graphite boat sheets are used under high temperature and high vacuum. If there are more impurities, a large amount of volatile substances will be easily formed at high temperature, which will not only increase the coating pretreatment time and affect production efficiency, but also affect the quality of some special products; 5. Lower thermal expansion coefficient and good seismic resistance to ensure stable size and good contact, and not to break under rapid cooling and heating; 6. Good mechanical strength to reduce breakage during operation.
[0005] Chinese patent CN115287632A discloses a graphite boat pretreatment method and a modified graphite boat, the pretreatment method comprising the following steps: (1) subjecting the graphite boat to a constant temperature treatment and a vacuum heating treatment; (2) subjecting the graphite boat treated in step (1) to a composite deposition coating treatment; (3) subjecting the graphite boat treated in step (2) to a vacuum and then introducing nitrogen, exiting the boat, and completing the pretreatment; the composite deposition coating treatment in step (2) comprises depositing an inner layer of silicon oxide and an outer layer of silicon nitride on the surface. Through the pretreatment before the existing saturation process, a dense inner layer of silicon oxide and an outer layer of silicon nitride with a stable film surface are coated on the surface of the graphite boat, which, on the one hand, prevents the graphite boat from overflowing with impurities, and at the same time can reduce the pollution of aluminum oxide during back coating, improve the uniformity of the aluminum oxide film, and reduce the occurrence of dark edges. However, this patent processes the graphite boat by coating, which may lead to uneven coating, cracking and peeling of silicon wafers and boat walls, reduced coating rate, and even inability to continue coating after the graphite boat is reused many times.
[0006] Chinese patent CN117800766A discloses a graphite evaporation boat and its preparation method, wherein a coating structure is formed on the evaporation side of the evaporation boat, and the coating structure includes the following components in mass fraction: 60%-80% matrix filler; 10-15% silicon; 1-5% nickel-aluminum composite powder; 10-15% thermal conductive filler; 0.5-2% adhesive; and the coating structure is formed by hot pressing and sintering at increasing temperatures in succession. The present invention is based on a multi-component coating, and the components are subjected to multiple hot pressing and sintering treatments at different temperatures, so that melt diffusion of different components is easily formed. The internal crystal components undergo multi-phase melting and reaction during the sintering process to gradually form a densified composite ceramic coating, which can improve the corrosion resistance of the graphite evaporation boat. However, this patent also performs coating treatment on the surface of the graphite material, and does not solve the problem of high porosity when preparing the graphite material. The above-mentioned coating peeling will also occur, resulting in the problem that the graphite boat cannot be coated.
[0007] Therefore, developing a graphite material with better performance for preparing graphite boats is of great significance to the art. Summary of the invention
[0008] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a low-porosity graphite material and a preparation method and application thereof. The graphite material has extremely low porosity as well as good mechanical properties and electrical conductivity, a small resistance change rate at high temperature, and a low thermal expansion coefficient, and is suitable for preparing graphite boat sheets for solar cell coating.
[0009] To achieve the above object, the present invention provides the following technical solutions:
[0010] A method for preparing a low-porosity graphite material comprises the following steps:
[0011] S1, pretreatment of natural flake graphite: purifying natural flake graphite and adding it into an acidic potassium permanganate solution for stirring and impregnation treatment, filtering, washing and drying after the treatment to obtain pretreated natural flake graphite;
[0012] S2, preparation of modified flake graphite: adding the pretreated natural flake graphite in step S1 to deionized water, then adding zirconium oxychloride, stirring evenly, adding ammonia water, carrying out a hydrothermal reaction, filtering, washing, and drying after the reaction is completed to obtain a solid powder; then adding the solid powder to anhydrous ethanol, then adding vinyl triethoxysilane, stirring at 50-60°C for 2-3h, then adding 2,3,4-trimethyl-2-pentene and azobisisobutyronitrile, carrying out a constant temperature reaction, filtering, washing, and drying after the reaction is completed to obtain a modified flake graphite;
[0013] S3, preparation of a mixture: grinding petroleum coke and asphalt coke to obtain a mixed powder, then adding the mixed powder, carbon black, and modified asphalt into a kneading pot and mixing them evenly, performing a primary kneading process; then adding the modified flake graphite in step S2, mixing evenly, performing a secondary kneading process, and obtaining a mixture;
[0014] S4, crushing and grinding: crushing the mixed material in step S3 and then grinding it for a second time to obtain abrasive;
[0015] S5, pressing and calcining: adding the abrasive in step S4 into a pressing machine for pressing to obtain a green body, and then calcining the green body to obtain a calcined material;
[0016] S6, impregnation and carbonization: adding the roasted material in step S5 to the modifier, and impregnating it at 50-60°C for 2-4h. After impregnation, take it out, put it into an impregnation tank, evacuate it, and then add it into molten modified asphalt for impregnation. After impregnation, carbonize it to obtain a carbonized material;
[0017] S7, graphitization: graphitizing the carbonized material in step S6 to obtain the low-porosity graphite material.
[0018] Preferably, the pH of the acidic potassium permanganate in step S1 is 3-4, the concentration of potassium permanganate is 40-60 g / L, the temperature of the stirring immersion is 30-40° C., and the time is 2-4 h.
[0019] More preferably, the purification process of the natural flake graphite in step S1 is: adding the natural flake graphite to a sodium hydroxide solution with a concentration of 0.5-1 mol / L, immersing it at 40-50°C for 1-2h, filtering and drying after immersion, calcining at 500°C for 2h, then adding it to a hydrochloric acid solution with a mass concentration of 10%, immersing it at a microwave power of 500W for 1h, filtering, washing and drying after immersion.
[0020] In the present invention, natural flake graphite is purified to increase the carbon content of the natural flake graphite, and is used as a raw material, so that the prepared graphite material has better electrical conductivity, and the problem of large porosity caused by impurities during graphitization can also be reduced. Subsequently, the purified natural flake graphite is subjected to acid oxidation treatment to increase the active oxygen-containing functional groups on the surface of the natural flake graphite, thereby improving the bonding force between the natural flake graphite and the modified asphalt, thereby improving the mechanical properties of the graphite material.
[0021] Preferably, the mass concentration of the ammonia water in step S2 is 10-15%, the mass ratio of the pretreated natural flake graphite, deionized water, zirconium oxychloride, and ammonia water is 50:800-1000:20-30:60-100, the temperature of the hydrothermal reaction is 140-170°C, and the time is 7-10h; the mass ratio of the solid powder, vinyltriethoxysilane, 2,3,4-trimethyl-2-pentene, and azobisisobutyronitrile is 50:7-11:5-9:0.3-0.6, the temperature of the isothermal reaction is 65-75°C, and the time is 2-3h.
[0022] In the present invention, natural flake graphite is modified to introduce zirconium oxide on the surface, and then double bonds are introduced by silane treatment, and finally 2,3,4-trimethyl-2-pentene is grafted. The introduction of zirconium ions can generate zirconium carbide in the subsequent graphitization process of the graphite material, thereby improving the hardness of the graphite material. At the same time, zirconium carbide also has an extremely high melting point, which can improve the heat resistance of the graphite material and increase the service life of the graphite material. The introduced 2,3,4-trimethyl-2-pentene contains hydrophobic chain alkanes, which have good compatibility with modified asphalt. During the kneading process, the modified flake graphite and the modified asphalt can be completely compatible, further improving the comprehensive performance of the graphite material. In addition, 2,3,4-trimethyl-2-pentene contains methyl side chains, and the side chain structure can increase the spatial stereoscopic properties of the molecule, resulting in a more complex and denser carbon atom connection mode between molecules, a higher residual carbon content, and a reduced porosity after carbonization, thereby improving the mechanical properties of the graphite material.
[0023] Preferably, the mass ratio of petroleum coke and asphalt coke in step S3 is 20:25-60, and the mass ratio of the mixed powder, carbon black, modified asphalt and modified flake graphite is 45-80:10-20:18-22:15-30; the temperature of the first kneading treatment is 120-140°C, and the time is 0.5-1h, and the temperature of the second kneading treatment is 160-180°C, and the time is 0.5-1h.
[0024] More preferably, in step S3, the mass ratio of petroleum coke to asphalt coke is 20:30-50, and the mass ratio of the mixed powder, carbon black, modified asphalt and modified flake graphite is 50-70:15-20:20-22:20-25; the temperature of the first kneading treatment is 130-140°C, and the time is 0.5-1h, and the temperature of the second kneading treatment is 170-180°C, and the time is 0.5-1h.
[0025] In the present invention, modified asphalt is used as a binder. Compared with coal tar pitch, modified asphalt has a higher residual carbon rate and good adhesion, and the ash content of modified asphalt is lower than that of coal tar pitch, which is more conducive to improving the performance of graphite materials.
[0026] Preferably, the particle size of the abrasive in step S4 is 5-15 μm; the pressing pressure in step S5 is 90-130 MPa, and the time is 1-2 h; the calcination temperature is 800-950° C., and the time is 3-5 days.
[0027] More preferably, the particle size of the abrasive in step S4 is 5-15 μm; the pressing pressure in step S5 is 100-120 MPa, and the pressing time is 1-1.5 h; the calcination temperature is 850-900° C., and the calcination time is 3-4 days.
[0028] Preferably, in step S6, the preparation method of the modifier is as follows: add 10-15g of Tween 80 to 300-400g of anhydrous ethanol, stir evenly, then add 20-30g of polyether-modified heptamethyltrisiloxane, and stir at 180-240r / min for 30-50min to obtain the modifier.
[0029] In the present invention, the roasted material is first impregnated in the modifier, and the function of the modifier is mainly to improve the wettability of the roasted material, so that in the subsequent modified asphalt impregnation process, the modified asphalt can better impregnate the roasted material and improve the bonding strength between the modified asphalt and the roasted material.
[0030] Preferably, in step S6, the vacuum is evacuated to 60-100 Pa, and the immersion conditions are 180-200° C. and 8-12 MPa for 12-18 hours; the carbonization temperature is 1000-1200° C., and the time is 20-30 days.
[0031] More preferably, in step S6, the vacuum is evacuated to 70-90 Pa, and the immersion conditions are 190-200° C. and 10-12 MPa for 12-16 hours; the carbonization temperature is 1100-1200° C., and the time is 20-25 days.
[0032] Preferably, the graphitization temperature in step S7 is 2600-2900° C. and the time is 30-40 days.
[0033] More preferably, the graphitization temperature in step S7 is 2700-2800° C. and the time is 30-35 days.
[0034] The present invention also protects a low-porosity graphite material prepared by the method as described above.
[0035] The present invention also protects the use of the low-porosity graphite material as described above in preparing graphite boat sheets.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) The low porosity graphite material provided by the present invention is prepared by modifying natural flake graphite and using it as a raw material for preparing graphite material. Natural flake graphite has good electrical and conductive properties, which can not only improve the comprehensive performance of the graphite material, but also avoid the problems of large porosity, low mechanical strength, poor oxidation resistance and thermal shock resistance of the graphite material due to the poor compatibility of natural flake graphite with modified asphalt after modification. The prepared graphite material not only has good thermal conductivity, but also has good mechanical properties and low expansion coefficient, and is particularly suitable for preparing graphite boat sheets, thereby increasing the service life of the graphite boat sheets.
[0038] (2) The low porosity graphite material provided by the present invention is prepared by first purifying natural flake graphite and then subjecting it to acid oxidation to increase the number of active oxygen groups on the surface of the flake graphite, which can not only improve the bonding force between the flake graphite and the modified asphalt, but also facilitate the subsequent reaction; then, zirconium oxide is in situ generated on the surface of the flake graphite by a hydrothermal method, thereby introducing the zirconium element, which can improve the heat resistance of the graphite material in the subsequent graphitization process, thereby improving the thermal shock resistance of the graphite material and reducing the expansion coefficient; then, the flake graphite is modified with vinyltriethoxysilane, on the one hand, the introduced silane makes the flake graphite have better dispersibility, and on the other hand, the introduced double bonds are conducive to the next reaction; finally, the flake graphite containing double bonds is reacted with 2,3,4-trimethyl-2-pentene to introduce hydrophobic branched alkanes on the surface of the flake graphite, and during the kneading process, the modified asphalt and the natural flake graphite can be completely compatible, thereby improving the comprehensive performance of the graphite material.
[0039] (3) The low porosity graphite material provided by the present invention is prepared by adding the calcined material into a modifier for impregnation treatment before impregnation with modified asphalt, so that the calcined material is more easily impregnated with the modified asphalt in the subsequent impregnation process, thereby improving the compatibility of the calcined material and the modified asphalt, thereby reducing the pores generated by uneven impregnation, and making the obtained graphite material have a lower porosity. DETAILED DESCRIPTION
[0040] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] In the present invention, natural flake graphite was purchased from Qingdao Mingrun Chenyue Graphite Co., Ltd., with a mesh size of 800 mesh;
[0042] Petroleum coke: particle size is -300 mesh, moisture ≤1%, ash ≤1%, low-sulfur cooked coke block;
[0043] Asphalt coke: particle size -300 mesh, moisture ≤1%, ash ≤1%, true density ≥1.98g / cm 3 , using low-sulfur coke blocks;
[0044] Modified asphalt: purchased from Hebei Hankai Energy Technology Development Co., Ltd., with a softening point of 105-115°C, a coking value of ≥56%, and quinoline insoluble matter ≤6%.
[0045] The polyether-modified heptamethyltrisiloxane was purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd. with a CAS number of 27306-78-1.
[0046] Example 1
[0047] A method for preparing a low-porosity graphite material comprises the following steps.
[0048] S1, pretreatment of natural flake graphite: 50g of natural flake graphite was added to a sodium hydroxide solution with a concentration of 0.8mol / L, impregnated at 45°C for 1.5h, filtered and dried after impregnation, calcined at 500°C for 2h, then added to a hydrochloric acid solution with a mass concentration of 10%, impregnated at a microwave power of 500W for 1h, filtered, washed and dried after impregnation to obtain purified natural flake graphite, then 50g of natural flake graphite was added to 500mL of acidic potassium permanganate solution (pH 3.5, potassium permanganate concentration of 50g / L), stirred and impregnated at 35°C for 3h, filtered, washed and dried after treatment to obtain pretreated natural flake graphite;
[0049] S2, preparation of modified flake graphite: 50g of pretreated natural flake graphite in step S1 is added to 900g of deionized water, followed by adding 25g of zirconium oxychloride, stirring evenly, adding 80g of ammonia water with a mass concentration of 15%, and hydrothermally reacting at 160°C for 8h. After the reaction is completed, filtering, washing, and drying are performed to obtain a solid powder; then 50g of the solid powder is added to 700g of anhydrous ethanol, followed by adding 10g of vinyltriethoxysilane, stirring at 55°C for 2.5h, and then adding 7g of 2,3,4-trimethyl-2-pentene and 0.5g of azobisisobutyronitrile, and reacting at a constant temperature at 70°C for 2.5h. After the reaction is completed, filtering, washing, and drying are performed to obtain modified flake graphite;
[0050] S3, preparation of a mixture: 200g of petroleum coke and 450g of asphalt coke were ground to obtain a mixed powder, and then 650g of the mixed powder, 150g of carbon black, and 200g of modified asphalt were added to a kneading pot and mixed evenly, and kneaded at 130°C for 1h; then 250g of modified flake graphite in step S2 was added, mixed evenly, and kneaded at 170°C for 0.5h to obtain a mixture;
[0051] S4, crushing and grinding: crushing the mixed material in step S3 and then grinding it for a second time to obtain an abrasive, the particle size of the abrasive is 5-15 μm;
[0052] S5, pressing and calcining: adding the abrasive in step S4 into a press, pressing at 120 MPa for 1.5 h to obtain a green body, and then calcining the green body at 900° C. for 4 days to obtain a calcined material;
[0053] S6, impregnation and carbonization: add 13g of Tween 80 to 350g of anhydrous ethanol, stir evenly, add 25g of polyether-modified heptamethyltrisiloxane, stir at 210r / min for 40min to obtain a modifier; add the calcined material in step S5 to the modifier, impregnate at 54°C for 3h, take out after impregnation, add to an impregnation tank, evacuate to 80Pa, then add molten modified asphalt for impregnation, impregnate at 190°C and 10MPa for 15h, and carbonize at 1100°C for 25 days after impregnation to obtain a carbonized material;
[0054] S7, graphitization: graphitizing the carbonized material in step S6 at 2800° C. for 35 days to obtain the low porosity graphite material.
[0055] Example 2
[0056] A method for preparing a low-porosity graphite material comprises the following steps.
[0057] S1, pretreatment of natural flake graphite: 50g of natural flake graphite was added to a sodium hydroxide solution with a concentration of 0.8mol / L, impregnated at 45°C for 1.5h, filtered and dried after impregnation, calcined at 500°C for 2h, then added to a hydrochloric acid solution with a mass concentration of 10%, impregnated at a microwave power of 500W for 1h, filtered, washed and dried after impregnation to obtain purified natural flake graphite, then 50g of natural flake graphite was added to 500mL of acidic potassium permanganate solution (pH 4, potassium permanganate concentration of 40g / L), stirred and impregnated at 30°C for 4h, filtered, washed and dried after treatment to obtain pretreated natural flake graphite;
[0058] S2, preparation of modified flake graphite: 50g of pretreated natural flake graphite in step S1 is added to 800g of deionized water, followed by adding 20g of zirconium oxychloride, stirring evenly, adding 60g of ammonia water with a mass concentration of 15%, and hydrothermally reacting at 140°C for 10h. After the reaction is completed, filtering, washing, and drying to obtain a solid powder; then 50g of the solid powder is added to 700g of anhydrous ethanol, followed by adding 7g of vinyltriethoxysilane, stirring at 50°C for 3h, and then adding 5g of 2,3,4-trimethyl-2-pentene and 0.3g of azobisisobutyronitrile, and reacting at a constant temperature of 65°C for 3h. After the reaction is completed, filtering, washing, and drying to obtain modified flake graphite;
[0059] S3, preparation of a mixture: 200g of petroleum coke and 250g of asphalt coke were ground to obtain a mixed powder, and then 450g of the mixed powder, 100g of carbon black, and 180g of modified asphalt were added to a kneading pot and mixed evenly, and kneaded at 120°C for 1h; then 150g of modified flake graphite in step S2 was added, mixed evenly, and kneaded at 160°C for 0.5h to obtain a mixture;
[0060] S4, crushing and grinding: crushing the mixed material in step S3 and then grinding it for a second time to obtain an abrasive, the particle size of the abrasive is 5-15 μm;
[0061] S5, pressing and calcining: adding the abrasive in step S4 into a pressing machine, pressing at 90 MPa for 2 hours to obtain a green body, and then calcining the green body at 800° C. for 5 days to obtain a calcined material;
[0062] S6, impregnation and carbonization: add 10g of Tween 80 to 300g of anhydrous ethanol, stir evenly, add 20g of polyether-modified heptamethyltrisiloxane, stir at 180r / min for 50min to obtain a modifier; add the calcined material in step S5 to the modifier, impregnate at 50°C for 4h, take out after impregnation, add to an impregnation tank, evacuate to 60Pa, then add molten modified asphalt for impregnation, impregnate at 180°C and 8MPa for 18h, and carbonize at 1000°C for 30 days after impregnation to obtain a carbonized material;
[0063] S7, graphitization: graphitizing the carbonized material in step S6 at 2600° C. for 40 days to obtain the low porosity graphite material.
[0064] Example 3
[0065] A method for preparing a low-porosity graphite material comprises the following steps.
[0066] S1, pretreatment of natural flake graphite: 50g of natural flake graphite was added to a sodium hydroxide solution with a concentration of 0.8mol / L, impregnated at 45°C for 1.5h, filtered and dried after impregnation, calcined at 500°C for 2h, then added to a hydrochloric acid solution with a mass concentration of 10%, impregnated at a microwave power of 500W for 1h, filtered, washed and dried after impregnation to obtain purified natural flake graphite, then 50g of natural flake graphite was added to 500mL of acidic potassium permanganate solution (pH 3, potassium permanganate concentration of 60g / L), stirred and impregnated at 40°C for 2h, filtered, washed and dried after treatment to obtain pretreated natural flake graphite;
[0067] S2, preparation of modified flake graphite: 50g of pretreated natural flake graphite in step S1 is added to 1000g of deionized water, followed by adding 30g of zirconium oxychloride, stirring evenly, adding 100g of ammonia water with a mass concentration of 10%, and hydrothermally reacting at 170°C for 7h. After the reaction is completed, filtering, washing, and drying to obtain a solid powder; then 50g of the solid powder is added to 700g of anhydrous ethanol, followed by adding 11g of vinyltriethoxysilane, stirring at 60°C for 2h, and then adding 9g of 2,3,4-trimethyl-2-pentene and 0.6g of azobisisobutyronitrile, and reacting at a constant temperature at 75°C for 2h. After the reaction is completed, filtering, washing, and drying to obtain modified flake graphite;
[0068] S3, preparation of a mixture: 200g of petroleum coke and 600g of asphalt coke were ground to obtain a mixed powder, and then 800g of the mixed powder, 200g of carbon black, and 220g of modified asphalt were added to a kneading pot and mixed evenly, and kneaded at 140°C for 0.5h; then 300g of modified flake graphite in step S2 was added, mixed evenly, and kneaded at 180°C for 1h to obtain a mixture;
[0069] S4, crushing and grinding: crushing the mixed material in step S3 and then grinding it for a second time to obtain an abrasive, the particle size of the abrasive is 5-15 μm;
[0070] S5, pressing and calcining: adding the abrasive in step S4 into a pressing machine, pressing at 130 MPa for 1 hour to obtain a green body, and then calcining the green body at 950° C. for 3 days to obtain a calcined material;
[0071] S6, impregnation and carbonization: add 15g of Tween 80 to 400g of anhydrous ethanol, stir evenly, add 30g of polyether-modified heptamethyltrisiloxane, stir at 240r / min for 30min to obtain a modifier; add the calcined material in step S5 to the modifier, impregnate at 60°C for 2h, take out after impregnation, add to an impregnation tank, evacuate to 100Pa, then add molten modified asphalt for impregnation, impregnate at 200°C and 12MPa for 12h, and carbonize at 1200°C for 20 days after impregnation to obtain a carbonized material;
[0072] S7, graphitization: graphitizing the carbonized material in step S6 at 2900° C. for 30 days to obtain the low porosity graphite material.
[0073] Comparative Example 1
[0074] A method for preparing a low-porosity graphite material comprises the following steps.
[0075] S1, pretreatment of natural flake graphite: 50g of natural flake graphite was added to a sodium hydroxide solution with a concentration of 0.8mol / L, impregnated at 45°C for 1.5h, filtered and dried after impregnation, calcined at 500°C for 2h, then added to a hydrochloric acid solution with a mass concentration of 10%, impregnated at a microwave power of 500W for 1h, filtered, washed and dried after impregnation to obtain purified natural flake graphite, then 50g of natural flake graphite was added to 500mL of acidic potassium permanganate solution (pH 3.5, potassium permanganate concentration of 50g / L), stirred and impregnated at 35°C for 3h, filtered, washed and dried after treatment to obtain pretreated natural flake graphite;
[0076] S2, preparation of a mixture: 200g of petroleum coke and 450g of asphalt coke were ground to obtain a mixed powder, and then 650g of the mixed powder, 150g of carbon black, and 200g of modified asphalt were added to a kneading pot and mixed evenly, and kneaded at 130°C for 1h; then 250g of the pretreated natural flake graphite in step S1 was added, mixed evenly, and kneaded at 170°C for 0.5h to obtain a mixture;
[0077] S3, crushing and grinding: crushing the mixed material in step S2 and then grinding it for a second time to obtain an abrasive, the particle size of the abrasive is 5-15 μm;
[0078] S4, pressing and calcining: adding the abrasive in step S3 into a pressing machine, pressing at 120 MPa for 1.5 h to obtain a green body, and then calcining the green body at 900° C. for 4 days to obtain a calcined material;
[0079] S5, impregnation and carbonization: add 13g of Tween 80 to 350g of anhydrous ethanol, stir evenly, add 25g of polyether-modified heptamethyltrisiloxane, stir at 210r / min for 40min to obtain a modifier; add the calcined material in step S4 to the modifier, impregnate at 54°C for 3h, take out after impregnation, add to an impregnation tank, evacuate to 80Pa, then add molten modified asphalt for impregnation, impregnate at 190°C and 10MPa for 15h, and carbonize at 1100°C for 25 days after impregnation to obtain a carbonized material;
[0080] S6, graphitization: graphitizing the carbonized material in step S5 at 2800° C. for 35 days to obtain the low porosity graphite material.
[0081] Comparative Example 2
[0082] A method for preparing a low-porosity graphite material comprises the following steps.
[0083] S1. Preparation of modified flake graphite: 50 g of natural flake graphite was added to 900 g of deionized water, followed by 25 g of zirconium oxychloride. After stirring, 80 g of 15% ammonia water was added. The mixture was hydrothermally reacted at 160° C. for 8 h. After the reaction was completed, the mixture was filtered, washed and dried to obtain modified flake graphite.
[0084] S2, preparation of a mixture: 200g of petroleum coke and 450g of asphalt coke were ground to obtain a mixed powder, and then 650g of the mixed powder, 150g of carbon black, and 200g of modified asphalt were added to a kneading pot and mixed evenly, and kneaded at 130°C for 1h; then 250g of modified flake graphite in step S1 was added, mixed evenly, and kneaded at 170°C for 0.5h to obtain a mixture;
[0085] S3, crushing and grinding: crushing the mixed material in step S2 and then grinding it for a second time to obtain an abrasive, the particle size of the abrasive is 5-15 μm;
[0086] S4, pressing and calcining: adding the abrasive in step S3 into a pressing machine, pressing at 120 MPa for 1.5 h to obtain a green body, and then calcining the green body at 900° C. for 4 days to obtain a calcined material;
[0087] S5, impregnation and carbonization: add 13g of Tween 80 to 350g of anhydrous ethanol, stir evenly, add 25g of polyether-modified heptamethyltrisiloxane, stir at 210r / min for 40min to obtain a modifier; add the calcined material in step S4 to the modifier, impregnate at 54°C for 3h, take out after impregnation, add to an impregnation tank, evacuate to 80Pa, then add molten modified asphalt for impregnation, impregnate at 190°C and 10MPa for 15h, and carbonize at 1100°C for 25 days after impregnation to obtain a carbonized material;
[0088] S6, graphitization: graphitizing the carbonized material in step S5 at 2800° C. for 35 days to obtain the low porosity graphite material.
[0089] Comparative Example 3
[0090] A method for preparing a low-porosity graphite material comprises the following steps.
[0091] S1, pretreatment of natural flake graphite: 50g of natural flake graphite was added to a sodium hydroxide solution with a concentration of 0.8mol / L, impregnated at 45°C for 1.5h, filtered and dried after impregnation, calcined at 500°C for 2h, then added to a hydrochloric acid solution with a mass concentration of 10%, impregnated at a microwave power of 500W for 1h, filtered, washed and dried after impregnation to obtain purified natural flake graphite, then 50g of natural flake graphite was added to 500mL of acidic potassium permanganate solution (pH 3.5, potassium permanganate concentration of 50g / L), stirred and impregnated at 35°C for 3h, filtered, washed and dried after treatment to obtain pretreated natural flake graphite;
[0092] S2, preparation of modified flake graphite: 50g of pretreated natural flake graphite in step S1 is added to 900g of deionized water, followed by adding 25g of zirconium oxychloride, stirring evenly, adding 80g of 15% ammonia water, and hydrothermally reacting at 160°C for 8h. After the reaction is completed, filtering, washing, and drying to obtain modified flake graphite;
[0093] S3, preparation of a mixture: 200g of petroleum coke and 450g of asphalt coke were ground to obtain a mixed powder, and then 650g of the mixed powder, 150g of carbon black, and 200g of modified asphalt were added to a kneading pot and mixed evenly, and kneaded at 130°C for 1h; then 250g of modified flake graphite in step S2 was added, mixed evenly, and kneaded at 170°C for 0.5h to obtain a mixture;
[0094] S4, crushing and grinding: crushing the mixed material in step S3 and then grinding it for a second time to obtain an abrasive, the particle size of the abrasive is 5-15 μm;
[0095] S5, pressing and calcining: adding the abrasive in step S4 into a press, pressing at 120 MPa for 1.5 h to obtain a green body, and then calcining the green body at 900° C. for 4 days to obtain a calcined material;
[0096] S6, impregnation and carbonization: add the roasted material in step S5 into an impregnation tank, evacuate to 80Pa, then add molten modified asphalt for impregnation, impregnate at 190°C and 10MPa for 15h, and after impregnation, carbonize at 1100°C for 25 days to obtain a carbonized material;
[0097] S7, graphitization: graphitizing the carbonized material in step S6 at 2800° C. for 35 days to obtain the low porosity graphite material.
[0098] The graphite materials prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests, wherein the bulk density was tested with reference to GB / T 24528-2009 "Determination Method for Bulk Density of Carbon Materials", the Shore hardness was tested with reference to GB / T 39535-2020 "Determination Method for Shore Hardness of Carbon Materials", the flexural strength was tested with reference to GB / T 3074.1-2021 "Determination Method for Flexural Strength of Carbon Materials", the compressive strength was tested with reference to GB / T 1431-2019 "Determination Method for Compressive Strength of Carbon Materials", the porosity was tested with reference to GB / T 24529-2009 "Determination Method for Apparent Porosity of Carbon Materials", the resistivity was tested with reference to GB / T 24525-2009 "Determination Method for Resistivity of Carbon Materials", the thermal conductivity was tested with reference to GB / T8722-2019 "Determination Method for Thermal Conductivity of Carbon Materials", and the thermal expansion coefficient was tested with reference to GB / T 3074.4-2016 "Method for Determination of Coefficient of Thermal Expansion (CTE) of Graphite Electrode", the test results are shown in Table 1:
[0099] Table 1
[0100]
[0101] It can be seen from Table 1 above that the low porosity graphite material provided by the present invention has good mechanical properties, good electrical and thermal conductivity, extremely low porosity and thermal expansion coefficient, and is particularly suitable for the preparation of graphite boat sheets and has good application prospects.
[0102] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a low-porosity graphite material, characterized in that: The following steps are involved: S1, pretreatment of natural flake graphite: purifying natural flake graphite and adding it into an acidic potassium permanganate solution for stirring and impregnation treatment, filtering, washing and drying after the treatment to obtain pretreated natural flake graphite; S2, preparation of modified flake graphite: adding the pretreated natural flake graphite in step S1 to deionized water, then adding zirconium oxychloride, stirring evenly, adding ammonia water, carrying out hydrothermal reaction, filtering, washing, and drying after the reaction is completed to obtain solid powder; then adding the solid powder to anhydrous ethanol, then adding vinyl triethoxysilane, stirring at 50-60°C for 2-3h, then adding 2,3,4-trimethyl-2-pentene and azobisisobutyronitrile, carrying out isothermal reaction, filtering, washing, and drying after the reaction is completed to obtain modified flake graphite; S3, preparation of a mixture: grinding petroleum coke and asphalt coke to obtain a mixed powder, then adding the mixed powder, carbon black, and modified asphalt into a kneading pot and mixing them evenly, performing a primary kneading process; then adding the modified flake graphite in step S2, mixing evenly, performing a secondary kneading process, and obtaining a mixture; S4, crushing and grinding: crushing the mixed material in step S3 and then grinding it for a second time to obtain abrasive; S5, pressing and calcining: adding the abrasive in step S4 into a pressing machine for pressing to obtain a green body, and then calcining the green body to obtain a calcined material; S6, impregnation and carbonization: adding the roasted material in step S5 to the modifier, and impregnating it at 50-60°C for 2-4h. After impregnation, take it out, put it into an impregnation tank, evacuate it, and then add it into molten modified asphalt for impregnation. After impregnation, carbonize it to obtain a carbonized material; S7, graphitization: graphitizing the carbonized material in step S6 to obtain the low porosity graphite material; In step S6, the preparation method of the modifier is as follows: add 10-15g of Tween 80 to 300-400g of anhydrous ethanol, stir evenly, then add 20-30g of polyether-modified heptamethyltrisiloxane, and stir at 180-240r / min for 30-50min to obtain the modifier.
2. The preparation method according to claim 1, characterized in that: In step S1, the pH of the acidic potassium permanganate is 3-4, the concentration of potassium permanganate is 40-60 g / L, the temperature of the stirring immersion is 30-40° C., and the time is 2-4 hours.
3. The preparation method according to claim 1, characterized in that: The mass concentration of the ammonia water in step S2 is 10-15%, the mass ratio of the pretreated natural flake graphite, deionized water, zirconium oxychloride, and ammonia water is 50:800-1000:20-30:60-100, the temperature of the hydrothermal reaction is 140-170°C, and the time is 7-10h; the mass ratio of the solid powder, vinyltriethoxysilane, 2,3,4-trimethyl-2-pentene, and azobisisobutyronitrile is 50:7-11:5-9:0.3-0.6, the temperature of the isothermal reaction is 65-75°C, and the time is 2-3h.
4. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of petroleum coke to asphalt coke is 20:25-60, and the mass ratio of the mixed powder, carbon black, modified asphalt and modified flake graphite is 45-80:10-20:18-22:15-30; the temperature of the first kneading treatment is 120-140°C, and the time is 0.5-1h, and the temperature of the second kneading treatment is 160-180°C, and the time is 0.5-1h.
5. The preparation method according to claim 1, characterized in that: The particle size of the abrasive in step S4 is 5-15 μm; the pressing pressure in step S5 is 90-130 MPa, and the time is 1-2 h; the calcination temperature is 800-950° C., and the time is 3-5 days.
6. The preparation method according to claim 1, characterized in that: In step S6, the vacuum is evacuated to 60-100 Pa, and the impregnation conditions are 180-200° C. and 8-12 MPa for 12-18 hours; the carbonization temperature is 1000-1200° C. and the time is 20-30 days.
7. The preparation method according to claim 1, characterized in that: The graphitization temperature in step S7 is 2600-2900° C. and the time is 30-40 days.
8. A low-porosity graphite material prepared by the method according to any one of claims 1 to 7.
9. Use of the low-porosity graphite material according to claim 8 in preparing graphite boats.
Citation Information
Patent Citations
Pretreatment method of graphite boat and modified graphite boat
CN115287632A
Graphite evaporation boat and preparation method thereof
CN117800766A
Preparation method of graphite radical composite material
CN101134675A
Method for manufacturing graphite material
JP2014181168A